The Comparison of Mind Mapping and Semantic Mapping to Enhance the Reading Comprehension - Musdalifah Musdalifah (Majesty Journal, 2019)
This study aimed to compare the effectiveness of Mind Mapping and Semantic Mapping in enhancing students’ reading comprehension and interest in learning English at SMA Muhammadiyah Kalosi, Enrekang Regency. The study employed a quasi-experimental design with cluster random sampling. The sample consisted of 72 second-grade students divided into two experimental classes, with 36 students in each class. The first class was taught through Mind Mapping, while the second class was taught through Semantic Mapping. The instruments used were a reading comprehension test and a questionnaire. The findings showed that both techniques improved students’ reading comprehension, but Mind Mapping produced better results. The mean score of the Mind Mapping class increased from 68.86 in the pre-test to 84.00 in the post-test, while the Semantic Mapping class improved from 69.00 to 76.97. Statistical analysis also showed a significant difference between the two groups in the post-test. In terms of learning interest, students taught through Mind Mapping demonstrated a higher level of interest than those taught through Semantic Mapping. Most students in the Mind Mapping class were categorized as highly interested, whereas most students in the Semantic Mapping class were in the moderate category. It can be concluded that Mind Mapping was more effective than Semantic Mapping in improving both reading comprehension and students’ interest in learning English.